The Asymmetric Effect of Sukuk on Government Budget: Dealing with Deficit in Malaysia - Seyf Eddine Benbekhti; Hadjer Boulila; Fethi Benladghem; Mohamed Benbouziane (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
Islamic economists sought to find transactions that fit and conform to the principles of Islamic religion, where Islamic bonds were one of the most critical products compatible with Islam. This study aims to shed light on the impact of Sukuk as one of the alternatives available for funding expenditures and deficit in Malaysia. This research using a non-linear autoregressive distributed lag model (NARDL) during the period 1990-2016. After identifying the asymmetric effect and the dynamic multiplier of Sukuk on government budget balance during the fluctuations of the exchange rate of the Ringgit, we have found that Islamic bonds are a very useful tool in financing deficit making Malaysia a pioneering experience in the field of Islamic engineering